Genetic parameters and genome-wide association studies including the X chromosome for various reproduction and semen quality traits in Nellore cattle - Felipe E. de Carvalho; José Bento S. Ferraz; Victor B. Pedrosa; Elisangela C. Matos; Joanir P. Eler; Marcio R. Silva; José D. Guimarães; Fernando Bussiman; Barbara C. A. Silva; Henrique A. Mulim; Artur Oliveira Rocha; Andre C. Araujo; et al. (BMC Genomics)
Abstract Background The profitability of the beef industry is directly influenced by the fertility rate and reproductive performance of both males and females, which can be improved through selective breeding. When performing genomic analyses, genetic markers located on the X chromosome have been commonly ignored despite the X chromosome being one of the largest chromosomes in the cattle genome. Therefore, the primary objectives of this study were to: (1) estimate variance components and genetic parameters for eighteen male and five female fertility and reproductive traits in Nellore cattle including X chromosome markers in the analyses; and (2) perform genome-wide association studies and functional genomic analyses to better understand the genetic background of male and female fertility and reproductive performance traits in Nellore cattle. Results The percentage of the total direct heritability (h2 total) explained by the X chromosome markers (h2 x) ranged from 3 to 32% (average: 16.4%) and from 9 to 67% (average: 25.61%) for female reproductive performance and male fertility traits, respectively. Among the traits related to breeding soundness evaluation, the overall bull and semen evaluation and semen quality traits accounted for the highest proportion of h2 x relative to h2 total with an average of 39.5% and 38.75%, respectively. The total number of significant genomic markers per trait ranged from 7 (seminal vesicle width) to 43 (total major defects). The number of significant markers located on the X chromosome ranged from zero to five. A total of 683, 252, 694, 382, 61, and 77 genes overlapped with the genomic regions identified for traits related to female reproductive performance, semen quality, semen morphology, semen defects, overall bulls’ fertility evaluation, and overall semen evaluation traits, respectively. The key candidate genes located on the X chromosome are PRR32, STK26, TMSB4X, TLR7, PRPS2, SMS, SMARCA1, UTP14A, and BCORL1. The main gene ontology terms identified are “Oocyte Meiosis”, “Progesterone Mediated Oocyte Maturation”, “Thermogenesis”, “Sperm Flagellum”, and “Innate Immune Response”. Conclusions Our findings indicate the key role of genes located on the X chromosome on the phenotypic variability of male and female reproduction and fertility traits in Nellore cattle. Breeding programs aiming to improve these traits should consider adding the information from X chromosome markers in their genomic analyses.